SMEs` Perception of Crowfunding in Indonesia - Fauji Sanusi; Agus David Ramdansyah; Yeni Januarsi (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyze not only awareness but also perceptions of small and medium enterprises in Indonesia, especially in Banten on two Fintech models, namely Peer-to-Peer lending and crowd funding in developing their business. By conducting survey on 115 SMEs, descriptive analysis was applied through Microsoft Office Excel data processing. Data analysis uses frequency distribution and central measurement. This research shows that there is still a lack of knowledge and awareness of Peer-to-Peer lending and crowd funding model which can be used as alternative financing instruments. Even so, some of them have a positive perception of development of FinTech. Thus, steps to increase awareness need to be carried out by related parties such as the government.